(untitled) (Vallis Aurea, 2023)
Contemporary business environment is characterized by frequent changes in business conditions. Technological innovations and changes in customers’ perception affect on the continuous improvement in quality, availability and functionality of the product. According to this, product life cycle is significantly reduced over time, so business entities are trying to deal with these changes. Due to this, business entities have to produce new products in very short time, but at the acceptable level of quality with minimum costs in order to maintain the required level of the product profitability. In order to achieve these objectives, business entities implement target costing and life cycle costing as management accounting methods. The main goal of this study is to present the potential model of integrated application of the target costing and life cycle costing. In this model target costing is focused on the products’ design phase in which all costs during the whole life cycle of a product are estimated. Using this model, business entities are able to maintain more quality cost management in order to achieve required profitability. This model enables the dynamic evaluation of the products’ profitability due to the fact it refers to the whole life cycle of the product.